A new species of Mesovelia (Heteroptera: Gerromorpha: Mesoveliidae) from South America, with identification key and notes on Colombian species - Floriano, Carla Fernanda Burguez; Moreira, Felipe Ferraz Figueiredo; Bispo, Pitágoras Da Conceição; Morales, Irina; Molano-Rendón, Fredy (Zootaxa, 2016)
Mesovelia tuberculata sp. nov. is described and illustrated based on material from the Pacific Region of Colombia. It can be recognized by the following characters of the male: mesofemur without a row of spinules; posterior margin of abdominal tergum VIII with a weak notch; abdominal pleuron VIII with an anterodorsal tubercle; abdominal sternum VI with the posteromedian projection rounded and fringed with black spinules; and paramere with margins converging and apex single. In addition, we present data concerning M. zeteki Harris & Drake and M. mulsanti White, and an identification key to species of Mesoveliidae from Colombia.